"Thinking outside the Yurt": Kazakhstani upper secondary school teachers' beliefs about the nature of creativity and creative students. (December 2022) - Ibrayeva, Laura; Helmer, Janet; CohenMiller, Anna
Highlights: Qualitative studies on creativity and teachers' beliefs about creativity in Kazakhstan and former-Soviet countries are minimal;. Regardless of the type of schools participants work at, their understanding about creativity and creative students were similar;. Beliefs about creativity shared by upper-secondary school teachers did not differ from teachers of primary and lower secondary school teachers in earlier research;. Participants' beliefs about creativity and creative students overlap not only with teachers' beliefs about creativity from other countries but also with the majority of creativity theories. Abstract: Creativity is connected with the prominent challenges of the 21 st century, such as unpredictability and complexity of a fast-changing, globalizing world. Possessing creative skills can help young people to navigate through uncertainty and fast paced changes. Therefore, the topic of creativity has received considerable attention and been studied extensively in education over the past few decades. However, in Kazakhstan and former-Soviet countries, there is minimal literature using qualitative studies on creativity in education, especially teachers' beliefs about creativity. It is commonly agreed that teachers behave according to their beliefs, with teachers' beliefs shaping and guiding their classroom practices. Teachers' beliefs about creativity can influence the effective implementation of creativity in the classroom with different studies on creativity demonstrating that teachers frequently do not have a clear understanding of what creativity is (Cho et al., 2017; Patston et al., 2021; Vincent-Lancrin et al., 2019). Teachers' lack of understanding of creativity means a possible lack of development of creativity in the classroom. This study presents Kazakhstani upper secondary school teachers' beliefs regarding the characteristics of creativity and creative students. We conducted a multiple case study involving four schools using semi-structured in-depth individual interviews with 15 Kazakhstani upper secondary school teachers. Findings of this study suggest that regardless of what type of schools participants work at and what subjects they teach, participants' beliefs about creativity and creative students overlap not only with teachers' beliefs about creativity from other countries but also with the majority of creativity theories.